The Information of Public Sciences: Definitions - Zaveckienė, Žiedonė (Knygotyra, 1988)
Many different conceptions are noticed in defining information: mathematical, cybernetic, philosophical, philological, and bibliographical directions. There are quantitative and qualitative definitions, ranging from very complicated to more or less simple, and very close to the primary one.The information of public sciences is very closely connected with information in general and especially with the information of social sciences, journalism, and bibliography.There is no consensus in defining social phenomena in general, which interferes with fixing the place of the information of public sciences. One can consider public and political information as synonyms for social information and define it as information on phenomena, facts, and documents of a social character. The information of public sciences can be defined as the information received in the process of cognition, including all the regularities, phenomena, facts, and also the documents of the public sphere.
Keywords: -